Strategy for monitoring and sustainable integrated control or eradication of Glossina brevipalpis and G.austeni (Diptera: Glossinidae) in South Africa - Scholtz, Clarke H. (University of Pretoria, 2013)
Thesis (PhD (Entomology))--University of Pretoria, 2005.